PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI MELALUI PERILAKU INOVATIF - Siska Debora; Amransyah; Efendi Rahmanto; Rizkiawan (Program Studi Manajemen, 2025)
This study aims to analyze the effect of intrinsic and extrinsic motivation on employee performance with innovative work behavior as a mediating variable in the General Affairs Subdivision of Equipment at the Regional Secretariat of East Kutai Regency. This research used a quantitative approach with an explanatory research design. Data were collected through questionnaires and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). The results show that intrinsic and extrinsic motivation have a positive effect on employee performance. Innovative work behavior also acts as a mediating variable that strengthens the relationship between work motivation and employee performance. These findings indicate that strengthening work motivation supported by innovative behavior can improve employee performance in local government institutions.